Egg Size and Early Nestling Growth in the Snow Petrel - Amundsen, Trond (The Condor, 1995)
I studied egg size variation, and the influence of egg size on early nestling growth, in Snow Petrels Pagodroma nivea breeding at Svarthamaren, Dronning Maud Land, Antarctica (71 degrees 53'S, 5 degrees 10'E). Egg sizes ranged from 36.4 to 52.1 cm(3), with a mean of 44.9 cm(3). Hatching occurred during 16-24 January, with a median hatching date of 20 January. Egg size had a significant effect on the body mass of hatchlings, explaining 30% of the variation in body mass of nestlings hatched within the last 24 hr, and 58% of the body mass variation of nestlings weighed while still slightly wet. An experiment, which included swapping of eggs between nests, together with analyses of non-manipulated nests, revealed an effect of egg size on nestling body masses at ages of two and four days. From the experiment, no effect of maternal quality as expressed by her egg size could be found. At an age of four days, 40% of the nestlings were left alone in the nest by their parents. Nestlings not attended by a parent at this age were significantly lighter than were those with parental company. Parents that had left their young by the time these were four days old may have been poor quality birds, as indicated by the tendency for such birds to have laid smaller eggs than had those still tending their young at the same nestling age.
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Regulation of parental investment in the Antarctic petrel Thalassoica antarctica: an exchange experiment - Andersen, Reidar; Sæther, Bernt-Erik; Pedersen, Hans Christian (Polar Biology, 1995)
An experiment was conducted on the Antarctic petrel to test whether the parents were able to respond to changes in food demand of their offspring. Two experimental groups were formed by replacing eight 20-day-old chicks with 10-day-old chicks, and vice versa. The growth rate of chicks in the experimental groups was compared with that in two control groups with chicks of known age. The growth rate of 10-day-old chicks in the nests of parents which initially had 20-day-old chicks did not differ significantly from that in their respective control groups. This indicates that those parents were able to raise a new young nestling, despite having already raised another chick from hatching to 20 days. However, the 20-day-old chicks placed in nests with 10-day-old chicks had a significantly lower growth rate than their control group. Feeding rate per day and nest did not differ significantly among any of the groups. This suggests that the observed difference in growth rate between 20-day-old chicks is related to a lower amount of food delivered per visit to experimental chicks. Thus, in the Antarctic petrel, the feeding rate apparently is not regulated by the status of the chick, but by the parents' ability to gather food or willingness to provide food for the chicks.
Keywords: Dronning Maud Land; NARE 1989/90; fugler; ornitologi; petreller; zoologi

Antarktispetrellen: Sydishavets miljøbarometer - Lorentsen, Svein-Håkon (Natur, 1995)
Keywords: Dronning Maud Land; zoologi

Reproductive effort in the Antarctic petrel Thalassoica antarctica : the effect of parental body size and condition - Lorentsen, Svein-Håkon (Norwegian Institute for Nature Research (NINA), 1995)
Keywords: Antarktis; fugler; ornitologi; petreller; reproduksjon; zoologi

Incubation and brooding performance of the Antarctic Petrel Thalassoica antarctica at Svarthamaren, Dronning Maud Land - Lorentsen, Svein-Håkon; Røv, Nils (Ibis, 1995)
Antarctic Petrel Thalassoica antarctica incubation and brooding effort was studied at Svarthamaren, Dronning Maud Land, during the austral summer of 1991-1992. The females probably left the nest site shortly after egg laying. The duration of incubation and brooding shifts as well as the daily weight loss (absolute and proportionate) were comparable with those of other similar-sized procellariform species. Males spent more time incubating and brooding than did females, suggesting higher female energy stress due to egg laying, Incubating birds which were below average weight were likely to desert the nests before their mates returned from feeding trips. Both males and females lost approximately one-fifth of their body-weight during their first incubation shifts. Nevertheless, they increased their initial weights from egg laying to hatching and had their highest initial weights when they returned to start the shift during which the egg hatched. No factors related to adult body-weight explained the duration of the incubation shifts, Both males and females gained weight at a higher rate when at sea than they lost it during incubation, and it is suggested that factors unrelated to food availability or individual feeding skills may be important in regulating the duration of the incubation shifts and the stay at sea.
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi; petreller; zoologi

Distribution and diving behaviour of crabeater seals (Lobodon carcinophagus) off Queen Maud Land - Nordøy, Erling S.; Folkow, Lars; Blix, Arnoldus Schytte (Polar Biology, 1995)
Eight crabeater seals (Lobodon carcinophagus) (three females, five males), ranging in body mass between 125 and 220 kg, were captured off Queen Maud Land (70-72 degrees S, 7-16 degrees W) during the last week of February, just after moulting, and tagged with Argos satellite-linked dive recorders to provide data on location and diving depth and duration. During the first few weeks of March the seals were moving in the pack ice along the continental shelf edge, close to the coast of Queen Maud Land. In April and May, when the pack ice extended northwards, most of the seals moved north, one reaching 63 degrees S in late May. In the first half of June the two remaining seals turned south and moved back deep into the pack ice. The seals made about 150 dives per day each throughout the study period. Ninety percent of these were made to depths of less than 52 m. Individual maximum diving depths varied between 288 and 528 m. In March the seals were most active at night, when the dive depth was shallower than during the day. In April and May the seals were more active during day-time, with an absence of any diurnal change in diving depth. These results support the notion that crabeater seals predominantly feed on krill in Antarctic pack ice, even when winter returns to the waters off Queen Maud Land.
Keywords: Dronning Maud Land; Sørishavet; Weddellhavet; biodiversitet; marin biologi; seler; telemetri; zoologi; økologi